2022
DOI: 10.1007/s10071-022-01621-9
|View full text |Cite
|
Sign up to set email alerts
|

Degraded and computer-generated speech processing in a bonobo

Abstract: The human auditory system is capable of processing human speech even in situations when it has been heavily degraded, such as during noise-vocoding, when frequency domain-based cues to phonetic content are strongly reduced. This has contributed to arguments that speech processing is highly specialized and likely a de novo evolved trait in humans. Previous comparative research has demonstrated that a language competent chimpanzee was also capable of recognizing degraded speech, and therefore that the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Bonobos have the largest vocal repertoire size of the nonhuman great apes 52 , and modify their communicative signals depending on social context 53,54,55 . In addition, multiple reports in a single bonobo support the notion that bonobos are able to understand spoken English words and sentences 56,57,58 , as well as degraded and computer-generated speech 59 . Thus, it is possible that FOXP2 alleles modulate FOXP2 expression in bonobos and that differential FOXP2 regulation impacts individual variability in bonobo vocal communication.…”
Section: Genetic Variationmentioning
confidence: 85%
“…Bonobos have the largest vocal repertoire size of the nonhuman great apes 52 , and modify their communicative signals depending on social context 53,54,55 . In addition, multiple reports in a single bonobo support the notion that bonobos are able to understand spoken English words and sentences 56,57,58 , as well as degraded and computer-generated speech 59 . Thus, it is possible that FOXP2 alleles modulate FOXP2 expression in bonobos and that differential FOXP2 regulation impacts individual variability in bonobo vocal communication.…”
Section: Genetic Variationmentioning
confidence: 85%
“…The first experiment found that dogs listened significantly longer to their own 16-channel vocoded name than the foil vocoded name when presented with both stimuli in natural speech and vocoded speech. This is similar to the stimulus sets used with Kanzi, a bonobo, and Panzee, a chimpanzee, where interleaved natural speech and vocoded speech were used in forced-choice paradigms (Heimbauer et al 2011 , 2021 ; Lahiff et al 2022 ). As was the case in prior degraded-speech processing studies using nonhuman animals, natural speech was included in this study because the intelligibility of distorted speech (e.g., sine-wave speech or vocoded speech) dramatically increases when people hear the natural version of the sentence prior to hearing the distorted version (Davis et al, 2005 ).…”
Section: Overall Discussionmentioning
confidence: 99%
“…This is in line with other studies from our lab demonstrating that dogs listen longer to their names than foil names in another version of degraded speech: speech in noise (Mallikarjun et al 2019 ). In all but one of the prior vocoded speech comprehension studies done with non-human animals, the target species were exposed to vocoded speech in a training/orientation period prior to testing their comprehension (Heimbauer et al 2021 ; Lahiff et al 2022 ; Shofner 2014 ; Shofner et al 2018 ). Panzee the chimpanzee was able to spontaneously recognize vocoded speech in a paradigm that also included trials with natural speech, as was tested in Experiment 1 with the dogs.…”
Section: Overall Discussionmentioning
confidence: 99%
See 2 more Smart Citations